KUKUM Artificial Marble - Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Shamsul Baharin, Jamaludin, Prof, Dr.; Che Mohd Ruzaidi, Ghazali, Prof. Madya; Khairul Nizar, Ismail, Dr.; Mohd Sobri, Idris; Mohd Nazry, Salleh (International Exhibition of Inventions, 2010)
Brig. Gen. Dato' Prof. Dr. Kamarudin Hussin and his team won gold at International Exhibition of Invention of Geneva 2006, 5th - 9th April 2006 was held at Palexpo, Geneva, Switzerland.